NEDD4 family E3 ligases in osteoporosis: mechanisms and emerging potential therapeutic targets - Heng Wu; Junhui Zuo; Yu Dai; Hairui Li; Song Wang (Journal of Orthopaedic Surgery and Research)
Abstract Osteoporosis is a systemic skeletal disorder characterized by reduced bone density and an increased risk of fractures, particularly prevalent in the aging population. Osteoporotic complications, including vertebral compression fractures, hip fractures, and distal forearm fractures, affect over 8.9 million individuals globally, placing a significant economic strain on healthcare systems. Recent advances have expanded our understanding of the mechanisms underlying osteoporosis, particularly the intricate regulatory networks involved in bone metabolism. A central player in these processes is ubiquitin-mediated proteasomal degradation, a crucial post-translational modification system that involves ubiquitin, the ubiquitin-activating enzyme (E1), ubiquitin-conjugating enzyme (E2), ubiquitin ligase (E3), deubiquitinating enzymes, and the proteasome. Among the various E3 ligases, the NEDD4 family has emerged as a key regulator of both bone development and osteoporotic pathology. This review delineates the role of NEDD4 family in osteoporosis and identifies potential drug targets within these pathways, offering insights into novel therapeutic approaches for osteoporosis through targeted intervention.